Application of nanotechnology in food engineering: a review (Research, Society and Development, 2022)
Nanotechnology can be defined as a generic expression of a complex of technologies, techniques and processes aimed at the development of new materials on a nanometric scale and can be applied in different industrial sectors, including foods. In view of the increased consumption of biodegradable products and its environmental aspects, several technologies have been used in the food industry, seeking to avoid the exaggerated production and waste, optimizing the production chain at different points where it can reduce the manufacturing cost, increase shelf life or add some functional ingredient. This study presents a review of a series of applications of nanotechnology in food production, especially in meat, dairy, sweets, fruits and vegetables, packaging and nanosensors.